THE CONTRIBUTION OF VIRTUAL REALITY TECHNOLOGY IN THE DEVELOPMENT TOURISM IN YOGYAKARTA - Muhammad Syaifulloh; Safor Mardianto (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
The tourism sector provides a significant contribution to the Gross Domestic Product (GDP) of the Republic of Indonesia, both through foreign exchange and economic turnover. Although the Indonesian tourism industry after the COVID19 pandemic has changed with an emphasis on green and clean products, it is hoped that this sector will be lessened by the community compared to the previous era. Research and development of VR has been carried out in various fields such as games, education, aviation, medicine, the application of VR in tourism is still common, there is a need to implement tourism while staying at home. The results of the systematic literature review conducted provide an explanation of the starting point for research by applying VR and making 3600 videos for industrial tourism.Keywords: Environmental Tourism, Virtual Reality, Video